Development of 4-DoF Robotic Arm Control System with Voice Command for Grasp Assistance - Assawasillapakul, Teerawit; Singkhleewon, Nutdanai; Thanasin, Kanlaya (วารสารวิจัย มทร. กรุงเทพ, 2023)
The objective of this research was to develop and examine the robotic arm system and speech recognition system controlled by microcontroller for object grasp control with voice command. The efficiency tests were movement efficiency of robotic arm, efficiency of speech recogniton system, and performance of robotic arm control with voice commands. The results revealed that robotic arm control with voice command system has the efficiency of robotic arm joints control for accurate movements in workspace as designed with 4 joints. In the speech recognition system, 10 voice commands were remembered to encode to the robotic arm control system efficiently with more than 90% accuracy. In consequence, the system that was developed can be used for grasp tasks in a robot workspace.